Cranial neural tube defect after trimethoprim exposure - Abdullah, Nor Linda (BMC Res Notes, 2018)
OBJECTIVES: The Neural Tube Defects Research Group of University of Malaya was approached to analyze a tablet named TELSE, which may have resulted in a baby born with central nervous system malformation at the University of Malaya Medical Centre. In this animal experimental study, we investigated the content of TELSE and exposure of its contents that resulted in failure of primary neurulation. RESULTS: Liquid Chromatography Tandem Mass spectrophotometry analysis of the TELSE tablet confirmed the presence of trimethoprim as the active compound. The TELSE tablet-treated females produced significant numbers of embryos with exencephaly (n = 8, 36.4%, *P < 0.0001), in all litters. The TELSE tablet-treated females subsequently given folic acid did not result in pregnancies despite there being evidence of possible resorption. Furthermore, after multiple rounds of mating which did not yield viable pregnancies, eventually, 2 embryos with exencephaly were harvested in a litter of 6 at 0.05% w/v pure trimethoprim once. The use of trimethoprim, a folic acid antagonist, peri-conceptionally increased the risk of exencephaly in the mouse. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13104-018-3593-1) contains supplementary material, which is available to authorized users.